Pengaruh Inovasi Produk, Branding Lokal dan Orientasi Pasar (Market Orientation) terhadap Daya Saing UMKM di Kabupaten Dompu - Jumratun Jumratun; Ega Saiful Subhan; Dian Urna Fasihat (Journal of Management and Creative Business, 2026)
This study aims to analyze the influence of product innovation, local branding, and market orientation on the competitiveness of UMKM in Dompu district. This study used a causal quantitative approach with a sample of 98 respondents selected through an accidental sample pen, a technique in which respondents were selected based on their availability and suitability with the research criteria. Data were collected using questionnaires and analyzed through multiple linear regression with the help of SPSS. The results of the study show that product innovation has a negative and significant effect on the competitiveness of UMKM, local branding has a positive and significant effect on the competitiveness of UMKM, while market orientation has a negative and significant effect on the competitiveness of UMKM. In addition, product innovation, local branding, and market orientation simultaneously have a significant effect on the competitiveness of UMKM. These findings show that effectively creating product innovation, local branding and market orientation are important factors in increasing the competitiveness of UMKM.